Handwashing Health Education to Prevent Covid-19 Transmission in SMP Inspirasi - Setiawan, Henri; Khairunnisa, Reffi Nantia; Oktavia, Windi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
COVID-19 is a disease caused by the SARS Cov-2 virus which can be transmitted through air or droplets. The palm of the hand is one of the members of the body that is most occupied by viruses, bacteria and microorganisms. To avoid the spread of the COVID-19 virus, you can wash your hands in 6 steps. This community service activity in the form of health education aims to improve the behavior of a clean and healthy life by washing hands in 6 steps. The service was carried out at Inspirasi SMP with a total of 76 participants. The material was delivered by lecturing using PowerPoint media plus discussion and question and answer sessions as well as the practice of washing hands in 6 steps. All participants can wash their hands properly according to the instructions and tutorials from the service team. As many as 65% of participants stated that this community service activity was very good and provided great benefits for preventing the transmission of COVID-19 at Inspiration Junior High School. The conclusion of this service activity was carried out smoothly and successfully. Efforts to prevent the transmission of COVID-19 need to be improved with continuous health education for various groups of society. So that nurses and other health workers can optimize preventive efforts as a counselor, negotiator, and educator